Impacts of rural - urban interaction on rural community, agricultural practices and mechanization, and land use : a case study of Bidayuh community in Kampung Stass, Kampung Skibang, Kampung Sebobok and Kampung Serasot, Bau - Polycarp, Maybal (Faculty of Social Sciences, 2005)
Impact of rural-urban interaction on agriculture are examined to identify and evaluate the characteristics of agrarian community in Kampung Stass, Skibang, Sebobok and Serasot, the agricultural mechanization, agriculture system as well as to determine the mode the rural-urban interaction and evaluate development of rural infrastructure.